Pengembangan Prasarana Masjid Untuk Taman Pendidikan Al-Qur’an (Tpa) Di Masjid Jamiatul Ihsan Sukabangun - Hendi Warlika Sedo Putra; Radius Pranoto; Anggi Nidya Sari; Viktor Suryan; Herlinawati Herlinawati (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2021)
This activity background to support the officer of Ihsan Sukajaya mosque, Sukarame, city of Palembang in design the infrastructure development. Hence, It considers better learning facilities. The steps are site visit, pra-design processes, detail engineering design, and budget planning. Field surveys are used to collecting data in a particular foundation area and analyze the existing condition. This result is a basic planning process to design the detailed drawing and cost estimate. The result of community service is a detailed drawing of mosque infrastructure development such as the main building of Taman Pendidikan Al-Quran, library, and office. This includes the budget planning